PENGGUNAAN METODE TRESHOLD GARCH DALAM MEMPREDIKSI HARGA SAHAM PT. GUDANG GARAM, Tbk. - Winata, Henry; Hapsari, Yudith Dyah (Optimum: Jurnal Ekonomi dan Pembangunan, 2017)
The cigarette industry in Indonesia continues to advance and evolve, it is supported by high demand by the public. PT. Gudang Garam, Tbk. is one of the companies that are already publicly traded in IDX (Indonesia Stock Exchange). The cigarette companyâs stock price tends to go up and make the tobacco companies have good potential in investing. This study uses time series analysis to forecast the stock price of PT. Gudang Garam, Tbk. Historical data is obtained from the stock price www. ï¬ nanceyahoo.com published by the Jakarta Stock Exchange. The results of this study indicate that the daily stock price data of PT. Gudang Garam, Tbk. during the period of 2010-2015 is the data that is contained heteroscedasticity and asymmetric shocks, so that we need the necessary variation model of ARCH / GARCH, Threshold GARCH (TGARCH) to produce accurate forecasting results. Results forecasting models indicate that the model TGARCH (1.1) is quite accurate in forecasting with a mean absolute percentage error of 4%.